2020
DOI: 10.3390/ijms21051732
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals Long Intergenic Non-Coding RNAs Contributed to Intramuscular Fat Content Differences between Yorkshire and Wei Pigs

Abstract: Intramuscular fat (IMF) content is closely related to various meat traits, such as tenderness, juiciness, and flavor. The IMF content varies considerably among pig breeds with different genetic backgrounds. Long intergenic non-coding RNAs (lincRNAs) have been widely identified in many species and found to be an important class of regulators that can participate in multiple biological processes. However, the mechanism behind lincRNAs regulation of pig IMF content remains unknown and requires further study. In o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 68 publications
5
17
0
Order By: Relevance
“…And other genes were mainly associated with diseases such as Mucopolysaccharidosis IIIB [23], stress-induced injury [24], oral-facial-digital syndromes [25], and breast cancer [26]. From the results, intramuscular related genes involved in fat and muscle related function were consistent with previous research, which reported that IMF is regulated through a complex pathway that interacts with muscle, fat, and connective tissue [27,28].…”
Section: Discussionsupporting
confidence: 86%
“…And other genes were mainly associated with diseases such as Mucopolysaccharidosis IIIB [23], stress-induced injury [24], oral-facial-digital syndromes [25], and breast cancer [26]. From the results, intramuscular related genes involved in fat and muscle related function were consistent with previous research, which reported that IMF is regulated through a complex pathway that interacts with muscle, fat, and connective tissue [27,28].…”
Section: Discussionsupporting
confidence: 86%
“…And other genes were mainly associated with diseases such as Mucopolysaccharidosis IIIB [29], stress-induced injury [30], oral-facial-digital syndromes [31], and breast cancer [32]. From the results, intramuscular related genes involved in fat and muscle related function were consistent with previous research, which reported that IMF is regulated through a complex pathway that interacts with muscle, fat, and connective tissue [33,34].…”
Section: Investigation Of Differential Expression Transcriptssupporting
confidence: 86%
“…Several studies on transcriptome profiling of porcine longissimus dorsi (LD) have been performed to investigate genes or pathways influencing IMF content in pigs. However, most of these studies have been carried out using pigs of different breeds ( Li et al, 2016 , 2020 ; Xu J. et al, 2018 ), with few studies on individuals of the same breed ( Lim et al, 2017 ; Muñoz et al, 2018 ) with distinct IMF content to identify consistent candidate genes. Hence, based on the RNA-seq, further studies using multiple analysis methods should be conducted to unravel genes and the pathways that regulate IMF contents.…”
Section: Introductionmentioning
confidence: 99%